Uma compreensão a partir de referente norte-americano do "Programa de Instrução Pública" de Aureliano Candido Tavares Bastos (1861-1873) - Souza, Josefa Eliana (2006)
The objective of this study is to understand the way Tavares Bastos dealt with Brazilian public education in the 60 s and in the beginning of the 70 s, in the XIX century, as for what he named the Brazilian public education program . It also tried to answer the following question: if and how did the author try to incorporate North-American models into the program of public education in Brazil? In order to perform such task, pamphlets the author/politician published between the years of 1861 and 1873 were examined. The analysis of such work allows identifying elements tha t are part of the program of public education aimed at by Tavares Bastos, and it emphasis that elements of the North- American models were used, mainly the one implemented by Horace Mann, and the ones presented by Aléxis Tocqueville, as an appropriate ama lgam to direct the Brazilian people towards the path of progress and civilization. By picking elements that constitute those models, Tavares Bastos built arguments in order to defend the idea of a free and universal school, mandatory education, co-education schools, and a teaching program dedicated mainly to knowledge based on practical principles that would provide the students with a kind of training that would be more adequate to the needs of workers from the fields of industry, commerce, and agriculture of that time. Therefore, the provinces should be equipped with schools whose mission would be preparing students to perform the tasks society demanded and to prepare them for democracy